Astrophysical jets from boosted compact objects - Cayuso, Ramiro (2019)
We perform full 3D numerical simulations of compact objects, such as black holes or neutron stars, boosted through an ambient forcefree plasma that posses a uniform magnetization. We study jet formation and energy extraction from the resulting stationary late time solutions. The implementation of appropriate boundary conditions has allowed us to explore a wide range of boost velocities, finding the jet power scales as γv2 (being γ the Lorentz factor). We also explore other parameters of the problem like the orientation of the motion respect to the asymptotic magnetic field or the inclusion of black hole spin. Additionally, by comparing a black hole with a perfectly conducting sphere in flat spacetime, we manage to disentangle curvature effects from those produced by the perfect conducting surface. It is shown that when the stellar compactness is increased these two effects act in combination, further enhancing the luminosity produced by the neutron star.